2021
DOI: 10.3390/plants10102168
|View full text |Cite
|
Sign up to set email alerts
|

Accelerating the Development of Heat Tolerant Tomato Hybrids through a Multi-Traits Evaluation of Parental Lines Combining Phenotypic and Genotypic Analysis

Abstract: The constitution of heat tolerant F1 hybrids is a challenge to ensure high yield and good fruit quality in the global climate. In the present work, we evaluated 15 genotypes for yield-related traits highly affected by high temperatures (HT). This phenotypic analysis allowed to identify four parental genotypes showing promising yield performances under HT conditions. Two of these genotypes also exhibited good fruit quality traits. A molecular marker analysis was carried out for six resistance genes to pathogens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 49 publications
(90 reference statements)
1
6
0
Order By: Relevance
“…Results showed that during the summer season, when temperatures were recorded to exceeded 32 °C with peaks of 38 °C, one genotype, named E42, exhibited a high and stable yield production (2.93 kg/plant) comparable to those of the tomato hybrids DOCET (3.13 kg/plant) and JAG8810 (3.37 kg/plant), reported to be heat-tolerant (Monsanto, unpublished results). Particularly, E42 stands out for the high number of total flowers and total number of fruits in all environments (open field, under tunnel), even when grown with one-month late transplant to increase exposure to high temperatures during reproduction [ 11 , 12 , 13 ]. These data were also confirmed by using a selection index based on fruit set, total number of fruits and yield production (both by Olivieri et al [ 13 ] and Ruggieri et al [ 12 ]), where the good performances of E42 were compared with 14 and 45 tomato lines, respectively.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Results showed that during the summer season, when temperatures were recorded to exceeded 32 °C with peaks of 38 °C, one genotype, named E42, exhibited a high and stable yield production (2.93 kg/plant) comparable to those of the tomato hybrids DOCET (3.13 kg/plant) and JAG8810 (3.37 kg/plant), reported to be heat-tolerant (Monsanto, unpublished results). Particularly, E42 stands out for the high number of total flowers and total number of fruits in all environments (open field, under tunnel), even when grown with one-month late transplant to increase exposure to high temperatures during reproduction [ 11 , 12 , 13 ]. These data were also confirmed by using a selection index based on fruit set, total number of fruits and yield production (both by Olivieri et al [ 13 ] and Ruggieri et al [ 12 ]), where the good performances of E42 were compared with 14 and 45 tomato lines, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Particularly, E42 stands out for the high number of total flowers and total number of fruits in all environments (open field, under tunnel), even when grown with one-month late transplant to increase exposure to high temperatures during reproduction [ 11 , 12 , 13 ]. These data were also confirmed by using a selection index based on fruit set, total number of fruits and yield production (both by Olivieri et al [ 13 ] and Ruggieri et al [ 12 ]), where the good performances of E42 were compared with 14 and 45 tomato lines, respectively. Francesca et al [ 14 ] compared physiological traits of E42 and the thermotolerant LA3120 (Malintka) genotype (Tomato Genetics Resource Center, TGRC, University of California, Davis, CA, USA) under heat stress.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The index selection approach is an effective approach in multicharacter-based selection. The effectiveness of this approach has been reported by Authrapun et al (2021), Olivieri et al (2021), andFarid et al (2021). Basically, index selection uses index values from a combination of several selection criteria with specific weighting values (Wang and Chen 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Analyses of reproductive thermotolerance has been carried out in several tomato genotypes, including cultivars [ 11 , 29 , 30 , 31 , 32 , 33 ], breeding lines [ 19 , 32 , 34 ] and wild relatives [ 7 , 35 ]. Up to date, few studies have addressed the response to heat in tomato landraces [ 36 , 37 ], those cultivated populations adapted to specific climatic and agronomic conditions and preserved by farmers [ 38 ].…”
Section: Introductionmentioning
confidence: 99%